2013
DOI: 10.1017/s0021932013000254
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Year Trend Analysis of Childhood Immunization Uptake and Coverage in Nigeria

Abstract: M u l t i -y e a r t r e n d an a l y s i s of c h i l d h o o d i m m u n i z a t i o n upt a k e and c o v e r a g e i n N i g e r i aOyelola A. Adegboye, Danelle Kotze a n d Olasunkanmi A. Adegboye Summary:As a leading indicator of child health, under-five mortality was incorporated in the United Nations Millennium Development Goals with the aim of reducing the rate by two-thirds between 1990 and 2015. Under-five mortality in Nigeria is alarmingly high, and many of the diseases that result in mortality are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 20 publications
4
19
0
Order By: Relevance
“…In line with this adjusted odds, the PAR analysis quantified what could be achieved if these variables are optimised and provided more explanation of the FIC variation like health system related factors being more influential in the rural area compared to urban. Overall, our results are in line with those from previous studies [6][7][8][9], based on more robust methodology we provided more details such as the association in the different places of residence and the improvement that could be obtained by ensuring all mothers obtain the level of the socio-demographic variable associated with optimum FIC.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In line with this adjusted odds, the PAR analysis quantified what could be achieved if these variables are optimised and provided more explanation of the FIC variation like health system related factors being more influential in the rural area compared to urban. Overall, our results are in line with those from previous studies [6][7][8][9], based on more robust methodology we provided more details such as the association in the different places of residence and the improvement that could be obtained by ensuring all mothers obtain the level of the socio-demographic variable associated with optimum FIC.…”
Section: Discussionsupporting
confidence: 89%
“…Nigeria has Africa's largest under age 1 year population, but one of the lowest immunisation coverage [4,5]; about 20% of the world's children under 1 year of age with incomplete DPT vaccination in 2017 lived in Nigeria [4]. Maternal education, antenatal care attendance and place of delivery, religion and place of residence have been reported to be associated with childhood vaccination in Nigeria [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There were also two publications 34,36 that implemented an intervention to generate evidence to improve newborn health. The existing interventions evaluated included: national emergency action plan to eradicate polio and prevention of maternal to child transmission of HIV.…”
Section: Resultsmentioning
confidence: 99%
“…Out of the 76 publications yielded in category 2, 7(9.2%) 30-36 satisfied the study inclusion criteria regarding newborn health and were selected (Table 2), while of the 249 publication from category 3, only 3 (1.2%) 37-39 met the study inclusion criteria regarding child health and were selected (Table 3). The flowchart of the study selection procedure is shown in Figure 1.…”
Section: Methodsmentioning
confidence: 99%